1981
DOI: 10.7326/0003-4819-94-1-31
|View full text |Cite
|
Sign up to set email alerts
|

Successful Outcome of Pregnancy in Women with Hypothyroidism

Abstract: Published data on the influence of hypothyroidism on fertility, gestation, and the offspring are controversial. We studied nine hypothyroid women during 11 pregnancies. Mean serum values for thyroxine, triiodothyronine (T3), resin T3 uptake ratio, and thyroid-stimulating hormone were 2.3 microgram/dL, 82 ng/dL, 0.64, and 105 mU/mL, respectively. Four patients had iatrogenic hypothyroidism (three remote thyroidectomy, one remote 131I therapy), two Hashimoto's thyroiditis, and three idiopathic primary hypothyroi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
43
0
5

Year Published

1985
1985
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(50 citation statements)
references
References 9 publications
2
43
0
5
Order By: Relevance
“…Perinatal outcomes reported in recent investigations (Montoro et al, 1981;Davis et al, 1988;Balen & Kurtz, 1990;Leung et al, 1993) have been more favourable than in earlier studies (Jones & Man, 1969).…”
Section: Discussionmentioning
confidence: 58%
“…Perinatal outcomes reported in recent investigations (Montoro et al, 1981;Davis et al, 1988;Balen & Kurtz, 1990;Leung et al, 1993) have been more favourable than in earlier studies (Jones & Man, 1969).…”
Section: Discussionmentioning
confidence: 58%
“…1 7 Neither of these earlier studies linked TSH measurements with pregnancy complications or outcome in the entire cohort. Other studies suggested that adverse events such as fetal death, premature birth, low birthweight, placental abruption, and pregnancy induced hypertension [8][9][10][11] occur more often in women with clinically diagnosed hypothyroidism. These observations, however, have been limited to women attending high risk or specialty clinics and may not reflect findings in the general population.…”
Section: Discussionmentioning
confidence: 99%
“…Dijstra et al (5) reported disturbed folliculogenesis and absence of corpora lutea when hypothyroidism was induced since birth. In women, hypothyroidism is associated with delay in the onset of puberty (6), anovulation (7), amenorrhea or hypermenorrhea, menstrual irregularity, infertility and increased frequency of spontaneous abortions (8)(9)(10). It was suggested that these alterations may be caused by a decrease in LH secretion.…”
Section: Introductionmentioning
confidence: 99%